Lexical Intertestimoniality and Chivalric Intertextuality: Echoes of the primitive Amadís in Pedro de Corral’s Crónica Sarracina (ca. 1430) - Romera Manzanares, Ana María (2023)
This work analyzes the intertestimonial variation that is documented between the terms brocal and cospe in a passage from the Crónica sarracina that requires amendment and whose investigation reveals not only lexical and variational data, but also the intertextuality that is present in certain chapters of the work by Pedro de Corral (ca. 1430). The documentation of these terms reveals that the primitive Amadís is one of the main sources for Corral’s text and that the author relies on this work’s initial version forsome fragments and, consequently, for the reproduction of these words, which have been distorted in textual tradition and barely documented in texts of the time with the registered sense and form.